Microplastic research trends in the Gulf region from a global perspective - Shabib, Ahmad; Reshadi, Mir Amir Mohammad; Maraqa, Munjed A.; Rezanezhad, Fereidoun (Frontiers in Environmental Science, 2024)
IntroductionMicroplastic (MP) pollution research has experienced significant global growth, with an exponential increase in publications since 2015. Despite this surge, research focused on the Gulf region remains limited. This gap is particularly concerning given the Gulf's dense industrial activities and substantial waste production. This study provides the first bibliometric analysis of MP research globally and within the Gulf region, examining the current state and emerging trends while identifying specific topics for future studies.MethodsA bibliometric analysis of peer-reviewed articles published between 2000 and 2024 was conducted for global and Gulf region research. Bibliometric analysis employed several tools to identify trends, keyword networks, and research gaps, with manual refinement of keywords to enhance accuracy. The study also analyzed leading countries and institutions contributing to MP research.Results and DiscussionThe analysis highlights significant global contributions, with China emerging as a leader in MP research globally and Iran playing a prominent role within the Gulf region. While global publications have increased exponentially since 2015, the Gulf region's research output remains underrepresented, accounting for only about 1.1% of global publications. This underscores the need for enhanced regional research to better integrate the Gulf into the global discourse on MPs. Keyword analysis reveals that certain areas of MP research remain unexplored in the Gulf region. The trend analysis shows an evolving focus globally, shifting from basic interactions of MPs with marine environments to more complex issues such as environmental health and ecosystem impacts. This progression indicates a maturing field that increasingly addresses the broader implications of MP pollution.